Macrointervention processes and strategies for leaders, changemakers, advocates, allies, and targets: A new framework to address macroaggressions in systems. (August 2021) - Awad, Michael N.; Crusto, Cindy A.; Hooper, Lisa M.
Abstract: The presence of macroaggressions, or obvious, overt, system-wide racial offensives and abusive acts evidenced in organizational systems and structures (e.g., confederate flags; signs in public places that read: "we only speak English"), have continued to penetrate American society at an unparalleled rate. The onslaught of violence toward racial, ethnic, and cultural minority citizens—in particular Black Americans and the disproportionate death rates of Black, Indigenous, and People of Color linked with the coronavirus disease 2019 (COVID-19) underscores an urgent need for broad-based systemic action. While microaggressions are well-documented in the psychological literature, less attention has been directed toward macroaggressions and how to address the ever-present forms of racism that propagate inequity within all aspects of organizations and larger systems (e.g., health care, legal, education). We propose a six-step conceptual framework to address macroaggressions evinced in these systems. Additionally, we introduce macrointervention strategies and illustrative examples that can be deployed and tested in diverse ecologies by institutional leaders, changemakers, advocates, allies, and targets of bias. We recommend well-designed empirical investigations to evaluate the proposed conceptual framework and to what extent it can affect changes at the macro-level.